2011
DOI: 10.1016/j.febslet.2011.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the unfolded protein response in Pichia pastoris requires splicing of a HAC1 mRNA intron and retention of the C-terminal tail of Hac1p

Abstract: a b s t r a c tWe have shown that the unfolded protein response (UPR) in Pichia pastoris requires splicing of a non-conventional intron in the HAC1 u mRNA in common with other eukaryotes. P. pastoris is a favoured yeast expression host for secreted production of heterologous proteins and the regulation of the UPR in P. pastoris may hold the key to its effective folding and secretion of proteins. We have also shown that the C-terminal region of the Hac1p from P. pastoris is required for functionality. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…Environmental factors are presumably responsible for the high level of UPR and ERAD related proteins in the batch phase in which high concentrations of glycerol were employed. Moreover, there are also - though not yet conclusive - indications that P. pastoris may exhibit in general a stronger constitutive or basal induction of the UPR as other yeast independent of the production of aberrant proteins [6,12,13]. Our findings also indicate that IP is a quite stable protein as it has been shown that the native-state stability of a secreted protein is inversely correlated to its UPR and ERAD inducing effect [5].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Environmental factors are presumably responsible for the high level of UPR and ERAD related proteins in the batch phase in which high concentrations of glycerol were employed. Moreover, there are also - though not yet conclusive - indications that P. pastoris may exhibit in general a stronger constitutive or basal induction of the UPR as other yeast independent of the production of aberrant proteins [6,12,13]. Our findings also indicate that IP is a quite stable protein as it has been shown that the native-state stability of a secreted protein is inversely correlated to its UPR and ERAD inducing effect [5].…”
Section: Discussionmentioning
confidence: 56%
“…Simplified, overloading of the secretory pathway is sensed in the ER by binding of KAR2 (or BiP) to folding intermediates or misfolded proteins which outcompete the binding of KAR2 to the ER luminal domain of IRE1 [11-13]. The release of KAR2 from the luminal IRE1 domain leads to conformational changes and autophosphorylation and subsequent activation of the cytosolic IRE1 endoribonuclease domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in S. cerevisiae , Guerfal et al (2010) reported that HAC1 is constitutively expressed and spliced in P. pastoris under normal growth conditions, which may explain the higher titers of secreted proteins obtainable with this organism. A contradictory observation was reported by Whyteside et al (2011). Un-spliced HAC1 mRNA was detected under normal growth conditions and splicing of HAC1 mRNA was only detected when cells were grown in presence of dithiothreitol (DTT) to activate the UPR.…”
Section: Basic Systems For Cloning and Expression In P Pastorismentioning
confidence: 73%
“…In contrast, the intron of Pichia pastoris HAC1 mRNA is 322 nt, which is longer than the S. cerevisiae HAC1 mRNA intron (10). Despite the differences in intron length, the HAC1 mRNAs of these yeast and filamentous fungi undergo similar, unconventional splicing reactions to produce functional Hac1 proteins (8,9,11).…”
mentioning
confidence: 83%